Does the single currency for EU resolve the exchange rate volatility and purchasing power parity puzzle? - Manzur, Meher; Chan, Felix (School of Economics and Finance, Curtin Business School, 2008)
This paper provides a new test of PPP and its relevance for the euro. Principal component analysis (PCA) is introduced to construct a ?pooled? measure of inflation for the 12 euro countries. This measure is used to test the PPP condition for the euro against three major currencies, namely, those of the USA, UK and Japan. The test results are then used to measure the speed of adjustment of the deviations from PPP using rolling and recursive regressions procedures. Finally, the forecasting accuracy of the PPP-based euro exchange rates is compared with those given by the random walk model, and the synthetic euro series provided by the European Central Bank. In general, the results are supportive of PPP.